N‐acetyl‐D‐glucosamine‐binding lectin (PrLec) from the serum of healthy blue swimming crab Portunus reticulatus agglutinates Gram‐positive (Micrococcus luteus) and Gram‐negative (Escherichia coli) bacteria. (3rd July 2022) - Ramaraj, Paulchamy; Bhuvaragavan, Sreeramulu; Sruthi, Kannan; Ranjana, Bhaskar; Subramanian, Kumarapuram Apadodharanan; Stella, Chellaiyan; Janarthanan, Sundaram
Abstract: Crabs are economically important crustaceans as they are essential delicacies consumed worldwide and are also an excellent environmental indicator. Portunus reticulatus, the blue swimming crab, is a highly valued seafood throughout Asia. The invertebrates protect themselves from invading pathogens by the innate immune response, and lectins play an essential role in recognizing non–self‐agents. The present study was aimed at purification and bacterial agglutinating properties of lectin from the serum of P. reticulatus . Initially, the species identity was confirmed using the mitochondrial cytochrome oxidase I (mtCOI) region and accessions were submitted to the NCBI and BOLD. Then, the lectin (PrLec) was purified using a chitosan‐based affinity column chosen based on the preliminary characterization consisting of haemagglutination (HA), cross‐adsorption, carbohydrate‐binding specificity and physicochemical parameters. The PrLec showed the highest HA titre value of 64 against Human A and buffalo erythrocytes and greater affinity towards N‐acetyl‐D‐glucosamine. The divalent cations and EDTA did not alter the PrLec activity. The molecular weight of the PrLec was 126 kDa (heterodimers of 66 and 60 kDa). Bacterial agglutination activity of the PrLec was examined with Gram‐negative bacteria, Escherichia coli and Gram‐positive bacteria, Micrococcus luteus . The lectin agglutinated both the bacterial strains efficiently.